Long-Term Follow-Up of Patients with West Nile Neuroinvasive Disease - Nataša Nikolić; Branko Milošević; Stojanović Miloš; Ljubisavljević Mila; Ivana Milošević; Nikola Mitrović; Jovan Malinić; Ana Filipović; Nevena Todorović; Uroš Karić; Boris Jegorović; Miloš Šabanović; et al. (Viruses)
Human West Nile virus (WNV) infection is usually asymptomatic. Less than 1% of patients develop neuroinvasive disease (WNND) which may result in permanent neurological impairment. The aim of this study was to assess the functional and cognitive status of patients with WNND approximately one year after the onset of symptoms. This prospective observational cohort study involved patients with WNND. Patients’ functional and cognitive abilities one year post-infection were assessed by telephone interviews using the Modified Rankin Scale (mRS), Barthel Index, and Telephone Interview for Cognitive Status. Sixty-two participants were analyzed. All patients had encephalitis, and 7 (11.3%) also had acute flaccid paresis/paralysis (AFP). At discharge, 40 (64.5%) patients had no or minimal neurological deficit (mRS 0–1), and 14 (22.6%) were functionally dependent (mRS 3–5). One year later, 52 (83.9%) patients were functionally independent (mRS 0–2), none was severely dependent (Barthel index 0–60), and 50 (90.9%) had a Barthel index score of 91–100. Among 14 functionally dependent patients at discharge, 3 (21.4%) remained functionally dependent one year later. During the follow-up, 7 (11.3%) patients died. No significant difference was observed in the fatality rate between patients with and without AFP, mRS 3–5 at discharge, or age over 65. The most common persistent symptoms were muscle weakness, walking instability, and issues with focus and memory. Using TICS, it was found that 33/55 patients (60%) had unimpaired and 2 (3.6%) had moderately or severely impaired cognitive status. The long-term prognosis after WNV encephalitis is satisfying. The majority of patients reached functional independence and 60% had unimpaired cognitive status.